An Adjacent Gray Code Pairing Approach for Fault Identification in Reversible Circuits - Kalita, Dimpimoni; Handique, Mousum (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2025)
The classical computing works on the concept of irreversibility increasing the heat dissipation in computing machinery. The remarkable ability of reversible computing is to reduce this dissipation of heat and to generate lossless information. The reversible circuit is the way to implement the reversible function. Therefore, the perfection of the functional behavior of the circuit plays a vital part within the realm of testing. Occurrence of faults in the reversible circuits creates a dysfunctional behavior in the circuit. Here in this study, a fault detection approach has been devised for reversible circuits that effectively identifies all categories of Missing Gate Faults (MGFs), such as single, multiple, partial, and repeated gate faults, through the use of the Adjacent Gray Code Pairing (AGCP) technique. The approach includes a process of conversion of binary to gray codes and pairing of non duplicative consecutive adjacent codes by which test vectors can be achieved for finding the respective faults with a 50% reduction in test set size. An experimental study and comparative analysis with existing methods have been carried out using a variety of standard reversible circuits.